Relationship between agronomic factors and level of damage by red squirrels to cocoa pods in the Cordillera de Mérida, Venezuela - Molina, Misael; Briceño, Jesús (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Cocoa is a tropical crop of great economic and ecological importance, with great potential in Venezuela, where fungal diseases and squirrels, among other factors, affect its productivity. The objective of the work was to analyze the relationship between the level of damage and some agronomic and environmental variables in 39 production of the state of Merida. The types of cocoa present were classified as criollo, forastero and hybrid. The damage percentages were transformed to arcsine and grouped into subjective categories according to the variables; the relationship was statistically analyzed using non-parametric tests: Kruskal-Wallis, Kolmogorov-Smirnov, and Moses, assuming a= 0.05. The level of damage was not statistically different (p> 0.05) between the crops located at different altitudes. The same occurred with the variables cocoa lot size, planting density, number of cultivars, level of agrochemicals, type of vegetation surrounding the crop, and distance to the forest. But the level of damage was statistically different (p< 0.05) between the production units that differed in the number of associated crops. The level of damage was also statistically different according to the number of shade trees.ha-1 and among those that differed with respect to the presence/absence of alternative fruits. It is concluded that the structural complexity of the crops functions as an integrating element in determining the level of damage caused by squirrels and defines the suitability of their habitat.